Pengelolaan Keuangan Bisnis Fashion PGB Merdeka Bogor - Efrita Norman (El-Mujtama: Jurnal Pengabdian Masyarakat, 2022)
This service aims to analyze and strengthen the financial management standards of the fashion business at PGB Merdeka, Bogor. The method used is a qualitative analysis with a participatory descriptive approach. The results of the service activities are as follows: From the aspect of bookkeeping administration, in general, bookkeeping has not been presented properly. There are owners who do the recording and there are those who do not record at all. For traders who have made records, bookkeeping administration is done simply. The bookkeeping is to record income, but not calculate the cost of goods sold. From assets that are not separated, sellers often experience confusion in the calculation. In terms of capital, besides their own capital, there are those who borrow money from banks and some goods are consigned. Business development that has been running, generally the owner is only motivated to increase sales turnover with unique and different items. In marketing, the owner can more freely determine the steps that must be taken so that his fashion can be known by the wider community, and the benefits are inventory turnover / up to date and trends.